A New Electrohydraulic Hybrid Energy-Saving System Used on the Reversible Rolling Mills. (9th February 2023) - Du, Rui; Liu, Zhiqi; Ge, Lei; Cui, Jinyuan; He, Lei
Abstract : In the face of the global energy crisis, the use of hybrid technology is an important way to achieve efficient energy storage and utilization. Hybrid systems have been successfully applied to automobiles and construction machinery, but no research study has been conducted on the design and application of energy recovery systems for reversible rolling mills. This article proposes a new type of noncoaxial parallel electrohydraulic hybrid drive system configuration for reversible rolling mills to save energy. It is proposed to collect the braking energy of the previous pass of the reversible rolling mill roll and the surplus power of the original primary drive motor and then start or accelerate the process for the next roll pass. A test experiment was established and the energy-saving efficiency of the proposed system was verified. By rolling 14 passes, 255.892 kJ of energy can be recovered. The overall energy efficiency rate is around 71.547%. The system will significantly promote energy saving, low carbon, green, and other aspects of the reversible rolling mills.